Spreading tourists around host countries of mega sport events: A strategy to overcome overtourism in host cities. (14th October 2019) - Mhanna, Rami; Blake, Adam; Jones, Ian
Abstract : Purpose: This study aims to recommend initiatives that can be adopted to overcome overtourism in host destinations of mega sport events. Design/methodology/approach: This study adopts a qualitative research design that involves 20 semi-structured interviews with key informant stakeholders of the London 2012 Olympic Games. An exploratory case study approach was used to investigate strategies used to leverage tourism benefits in host destinations, and the authors used thematic analysis to present strategies to overcome overtourism in host cities. Findings: This study emphasises the need for spreading tourists beyond the host city as a main strategy. To do so, three initiatives are recommended: spreading domestic tourism outside the host city, showcasing destination beyond the host city and promoting regional collaboration. Practical implications: This research provides tourism practitioners and destination management organisations in host destinations of mega sport events with an advanced strategic insights to capitalise on mega sport events. The authors suggest considering the events as a theme through an event planning process to overcome potential overtourism in unique host cities. Originality/value: As overtourism has an impact on visited destinations, this study argues that overtourism can be generated by mega sport events. This paper offers an extended insight into overcoming overtourism by implementing strategic event tourism, leveraging initiatives that can be extended in use to reach geographic areas beyond host cities of mega sport events.